Development of Food Plot at The South China Sea of Indonesia's Outer Island - Lukman Hakim, Dani (Inovbook Publications, 2025)
Establishing food plot in the outer island of Indonesia constitutes a strategic approach to bolstering food security and promoting agricultural sustainability. This study investigates the establishment and consequences of food plot on diverse remote islands in Indonesia. The key objectives encompass assessing soil suitability, determining appropriate crop selection, and implementing agricultural practices tailored to specific local climatic and environmental conditions. The study utilizes a mixed-methods methodology, incorporating soil analysis, crop yield evaluations, and interviews with local farmers and agricultural specialists. There are 14 SMUs in Anambas Islands Regency, that are created by layering various thematic maps such as those showing soil composition, topographic features, land use patterns, and climate data, including precipitation levels. Based on the results of the analysis of field and laboratory data, the actual land suitability class for lowland rice commodities was obtained based on the existing potential in the Anambas Islands Regency Area. From the existing soil map units (SMU), all SMU representative points are declared